2022
DOI: 10.1088/1612-202x/ac72aa
|View full text |Cite
|
Sign up to set email alerts
|

Real-time methods of hydrogen sulfide detection

Abstract: A comparative analytical review of existing methods and means of measuring hydrogen sulfide content in gasses was performed. The method of infrared laser absorption spectroscopy, which uses semiconductor diode lasers tunable in the mid-infrared range as emission sources, is proving to be one of the most promising methods for solving these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…The membranes used for the removal, separation, concentration, analysis, and valorization of hydrogen sulfide are based on ionic polymers [ 37 , 38 ], biopolymers [ 39 , 40 ], organic [ 41 ], or inorganic composites [ 42 ]. Among the ionic polymers, sulfonated polyether ether ketone and sulfonated ethylene–propylene–diene terpolymer (sEPDM) are used [ 43 ], while among biopolymers, chitosan (Chi) is of particular interest, because it covers various membrane separations and spans the membranes for sensors [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…The membranes used for the removal, separation, concentration, analysis, and valorization of hydrogen sulfide are based on ionic polymers [ 37 , 38 ], biopolymers [ 39 , 40 ], organic [ 41 ], or inorganic composites [ 42 ]. Among the ionic polymers, sulfonated polyether ether ketone and sulfonated ethylene–propylene–diene terpolymer (sEPDM) are used [ 43 ], while among biopolymers, chitosan (Chi) is of particular interest, because it covers various membrane separations and spans the membranes for sensors [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…As noted in our previous papers [1,2], the objective of developing a method for real-time detection of hydrogen sulfide (H 2 S) in gaseous media (in man-made emissions of industrial enterprises, in residential areas) is an important practical problem, in particular, for the gas, food industry, agriculture, environmental monitoring, etc. This is due to the fact that, being a highly dangerous toxic substance [3], hydrogen sulfide, when ingested into the human body, can cause pulmonary edema with the subsequent development of paralysis.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis of the currently existing H 2 S detectors conducted in [1,9] showed that the most common among them are semiconductor and electrochemical gas analyzers. These gas analyzers have both unquestionable advantages (high sensitivity, above all) and disadvantages, the main of which are limited selectivity, a noticeable effect on the measurement accuracy of external conditions, such as humidity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of H 2 S sensors have been proposed and used to address these requirements. 13,14 The most common H 2 S sensors are based on semiconducting metal oxides; they have low costs and are operated rapidly and easily. 15−17 However, metal oxide semiconductor (MOS) gas sensors typically have poor selectivity because they react to all reducing or oxidizing gases.…”
mentioning
confidence: 99%
“…Various types of H 2 S sensors have been proposed and used to address these requirements. , The most common H 2 S sensors are based on semiconducting metal oxides; they have low costs and are operated rapidly and easily. However, metal oxide semiconductor (MOS) gas sensors typically have poor selectivity because they react to all reducing or oxidizing gases. , Electrochemical sensors are also commercialized, but they are less sensitive than MOS gas sensors and susceptible to temperature and humidity changes. , Other types of H 2 S sensors have been proposed, such as colorimetric sensors, surface acoustic wave gas sensors, and sensors made using conductive materials (e.g., graphenes and polymers). , However, these sensors are hindered by challenges related to selectivity or ppb-level detection. Decorating conducting materials, such as MOS, , graphenes, and carbon nanotubes (CNTs), with metal and MOS nanoparticles (NPs) has recently been used to achieve sensor selectivity and ppb-level detection.…”
mentioning
confidence: 99%